IDENTIFICATION OF FUNGI IN CAMPUS TOILET BATHROOM WATER - Rizkha Cahya Maulida; Syafrina Sari Lubis; Muslich Hidayat (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The recognition of the health risks associated with fungal contamination in water is increasingly important in terms of microbiological safety and water quality. Fungus is one type of microorganism that can cause disease in humans. As cosmopolitan living things, fungi can be found anywhere close to human existence, be it in water, soil, air, or even in the human body. The purpose of this study was to determine the total number of colonies and the characteristics of pathogenic fungi in bathroom water at UIN Ar-Raniry campus public toilet facilities. This study used bathroom water samples taken at 5 different points. Water samples were taken as much as 0.5 ml and then isolated into Potato Dextrose Agar (PDA) media using the spread plate method. After 7 days of incubation, the total number of colonies was counted and the identification of the fungi was carried out to determine the macroscopic and microscopic characteristics of the fungi. The results of the study of fungal isolation on PDA media were the total colonies obtained from 5 different locations, namely 60 colonies, 47 colonies, 25 colonies, 29 colonies and 46 colonies. The identification results of 31 pure isolates found species namely Aspergillus sp., Aspergillus niger, A. fumigatus, A. flavus, Penicillium sp., and Mucor sp.